Molecular analysis of mitochondrial Complex V in gliomas of patients treated at a referral hospital in Pará State, Brazil (Research, Society and Development, 2022)
The objective of the present study was to evaluate mutations and polymorphisms in Complex V of the Mitochondrial DNA and its relationship with the emergence and progression of Glial tumors of the Central Nervous System in patients treated at a Reference Hospital for Oncological Treatment in Belém, Pará State, Brazil. Twenty-two tumor samples from the human nervous system were used, classified as astrocytomas of different degrees, where only two samples showed nucleotide alterations, and most patients over 50 years old are related to high-grade tumors and those below 50 years old are related to low-grade tumors, strengthening the idea that most low-grade astrocytomas are of hereditary origin and most of the emergence of high-grade ones are related to long-term exposure to carcinogenic agents. The alterations do not appear to interfere directly with the gene's function. Although mtDNA is more susceptible to mutations than nDNA, the results of this study suggest that the V complex remains intact even in a reactive environment, suggesting a protective mechanism, guaranteeing energy production in the tumor cell.